William Woodward : American Impressionist. - Hinckley, Robert C. (University Press of Mississippi, 2011)
William Woodward (1859-1939) was a force in New Orleans and the art world, and his legacy endures. In this first compilation of examples of Woodward's work spanning his career, essayists offer unique perspectives on the artist and his art. Woodward was a graduate of the Rhode Island School of Design and the Massachusetts Normal Art School. He started the School of Art and organized the Department of Architecture at Tulane University, and he taught evening art classes to citizens of New Orleans. His oil crayon paintings of the French Quarter were instrumental in preserving the French Quarter.